Hysteroscopy-guided natural orifice repair of isthmocele - Cihan Kaya; Özgür Aslan; Mülayim Tetik (Wolters Kluwer Medknow Publications, 2022)
Isthmocele can be defined as a hypoechoic field within the lower uterine segment, indicating a discontinuation of the myometrium at the uterine scar of a previous cesarean section. Postmenstrual spotting, pelvic pain, dysmenorrhea, dyspareunia, uterine rupture, cesarean scar pregnancy, and secondary infertility could be seen as the complications of existing isthmocele. Such defects are prevalent with the increasing number of cesarean deliveries. A 39-year-old woman who had three prior cesarean sections complaining irregular uterine bleeding for 2 years was examined. A uterine scar defect was observed. A hysteroscopy-guided natural orifice approach was planned to repair the defect. The patient was discharged without any complication in her postoperative 6th h. She had no pain or irregular bleeding in her 2-week postoperative visit.